Development e-LKPD Based Lesson Study For Learning Community (LSLC) On the Material of Reaction Rate Factors to Support Science Literacy Learners: Penelitian - Rifka Yulfanny; Fuldiaratman; Asmiyunda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a Research and Development (R&D) study using the Lee & Owens development model consisting of the analysis stage, the planning stage (design), development (development), implementation (Implementation) and evaluation (Evaluation). This study aims to produce a valid science literacy e-LKPD based on lesson study for learning community. The development pattern of this science literacy LKPD itself refers to the lesson study for learning community (SLSC) which consists of planning, implementation, and reflection. This research was conducted at SMAN 1 Muaro Jambi with the research subjects being class XI Phase F4. The instruments used were teacher interview sheets, validation questionnaires including material expert validation questionnaires to validate the feasibility of material content, and media expert validation questionnaires to validate the feasibility of media design, teacher assessment questionnaires and student response questionnaires. The data obtained were analyzed using qualitative and quantitative descriptive analysis techniques. The results of the study inform that the developed e-LKPD has been proven to be very valid with a percentage of 10% by media experts and 10% material, a practicality assessment of 10% by chemistry subject teachers, and also this teaching material is practical to use by students with a practicality percentage of 10%. From the results of the study, it can be concluded that the developed teaching material is suitable for use in the chemistry learning process, especially the material on reaction rate factors.